Patterns of age disparities in colon and lung cancer survival: a systematic narrative literature review - Pilleron, S; Gower, H; Janssen-Heijnen, M; Signal, V; Gurney, J; Morris, EJA; Cunningham, R; Sarfati, D (BMJ Publishing Group, 2021)
Objectives To identify patterns of age disparities in cancer survival, using colon and lung cancer as exemplars.